Factors Affecting Business Performance and Enhancing Competitiveness for Company in Vietnam - Case of Quang Ngai Agricultural Products and Food JSC - DAT, NGUYEN VAN; NHI, DUONG THI AI (The journal of contemporary issues in business and government, 2021)
Business performance will be reflected via measures such as stock price, revenues and net profits, etc.To be more competitive and have better performance, there are several factors that affect firm performance which need to be measured. We mainly use combination of quantitative methods (statistics, calculation formulas) with OLS regression and qualitative methods including synthesis, inductive and explanatory methods. The research findings in the case of Quang Ngai Agricultural Products and Food JSC (APF) tell us that For internal factors: R, Rf and CPI has positive correlation with APF stock price. For external factors: exchange rate has more impacts (negative relationship) on stock price. Besides, this study also give out recommendations for enhancing competitiveness and business performance.